Management practices and problems of egg production in Malaysia : a case study in Selangor. - Oh, B. T.; Choo, M. H. (1979)
A comprehensive field study focusing on the management practices and the problems faced by egg farmers,based on 20 egg-producing farms with flocks ranging 3000 to 50 000 layers was conducted in 1978,in Sungai Buloh near metropolitan Kuala Lumpur. The paper is divided into three part: 1) the problem setting,viz. the farmers,their management practices,and their levels and sources of technical knowledge; 2) detailed production costs and revenue breakdown of the sampled farms;and 3) the results and implications of the study.